A 55-Year-Old Man with Stage IV Squamous Cell Carcinoma of the Right Groin after External Beam Radiation for Testicular Cancer. (15th June 2014) - Ibilibor, Christine; Wells, Jeremy; Kavuri, Sravan; Moses, Kelvin A.
Abstract : Treating testicular cancer with adjuvant radiation has been associated with a number of second malignancies affecting the genitourinary tract and retroperitoneal structures; however, there have been few reported cases of cutaneous second malignancies. We report the case of a man who developed stage IV squamous cell carcinoma (SCC) of a condyloma after orchiectomy and adjuvant radiation for testicular cancer. We also review relevant literature available to date. A 55-year-old Caucasian man presented to the hospital with a large growth at the right groin which had grown into his right thigh preventing ambulation. His past medical history was significant for right testicular cancer of unknown pathology treated with orchiectomy and adjuvant radiation twenty years ago. Punch biopsy of the lesion revealed superficially invasive squamous cell carcinoma. He underwent excision of the growth with subsequent Cisplatin, radiation boost, and Paclitaxel regimens. Despite an aggressive treatment regimen and an initial good response, the patient's cancer progressed requiring palliative care. It is unclear whether or not therapeutic radiation in this case promoted the conversion of the patient's condyloma to a malignant lesion. Further studies are required at this time to clarify the clinical implications of these findings.